2021
DOI: 10.1038/s41467-021-24979-9
|View full text |Cite
|
Sign up to set email alerts
|

Seven-month kinetics of SARS-CoV-2 antibodies and role of pre-existing antibodies to human coronaviruses

Abstract: Unraveling the long-term kinetics of antibodies to SARS-CoV-2 and the individual characteristics influencing it, including the impact of pre-existing antibodies to human coronaviruses causing common cold (HCoVs), is essential to understand protective immunity to COVID-19 and devise effective surveillance strategies. IgM, IgA and IgG levels against six SARS-CoV-2 antigens and the nucleocapsid antigen of the four HCoV (229E, NL63, OC43 and HKU1) were quantified by Luminex, and antibody neutralization capacity wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
119
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(148 citation statements)
references
References 53 publications
16
119
0
1
Order By: Relevance
“…A few population-based SARS-CoV-2 sero-studies have been conducted since the beginning of the pandemic (for review see [ 2 ]), most of them reporting sero-prevalences during or after the first wave. Up to now, only the Spanish national study reported the results of their follow-up data [ 25 ] with a sero-prevalence at follow-up (November 2020) of 5%, and thus comparable to our results.…”
Section: Discussionsupporting
confidence: 90%
“…A few population-based SARS-CoV-2 sero-studies have been conducted since the beginning of the pandemic (for review see [ 2 ]), most of them reporting sero-prevalences during or after the first wave. Up to now, only the Spanish national study reported the results of their follow-up data [ 25 ] with a sero-prevalence at follow-up (November 2020) of 5%, and thus comparable to our results.…”
Section: Discussionsupporting
confidence: 90%
“…The baseline study population included randomly selected HCW from HCB who delivered care and services directly or indirectly to patients. Detailed characteristics of the study cohort have been described elsewhere [36][37][38]. Participants were recruited at the peak of the first wave of the pandemic in Spain (study month 0, M0) [36] and performed 2 additional visits at study month 1 (M1) and month 6 (M6) [37].…”
Section: Study Design Population and Settingmentioning
confidence: 99%
“…Detailed characteristics of the study cohort have been described elsewhere [36][37][38]. Participants were recruited at the peak of the first wave of the pandemic in Spain (study month 0, M0) [36] and performed 2 additional visits at study month 1 (M1) and month 6 (M6) [37]. Participants with any previous evidence of SARS-CoV-2 infection were invited to participate at study months 3 (M3) [38] and 9 (M9) follow-up visits.…”
Section: Study Design Population and Settingmentioning
confidence: 99%
See 2 more Smart Citations